Neck Pain Following Cervical Laminoplasty: Does Preservation of the C2 Muscle Attachments and/or C7 Matter? - Riew, K. Daniel; Raich, Annie L.; Dettori, Joseph R.; Heller, John G. (Evidence-Based Spine-Care Journal, 2013)
Study Design Systematic review.Objective In patients aged 18 years or older, with cervical spondylotic myelopathy or ossification of the posterior longitudinal ligament (OPLL), does sparing the C2 muscle attachments and/or C7-preserving cervical laminoplasty lead to reduced postoperative axial pain compared with conventional C3 to C7 laminoplasty? Do these results vary based on early active postoperative cervical motion?Methods A systematic review of the English-language literature was undertaken for articles published between 1970 and August 17, 2012. Electronic databases and reference lists of key articles were searched to identify studies evaluating C2/C3- or C7-preserving cervical laminoplasty for the treatment of cervical spondylotic myelopathy (CSM) or OPLL in adults. Studies involving traumatic onset, cervical fracture, infection, deformity, or neoplasms were excluded, as were noncomparative studies. Two independent reviewers assessed the level of evidence quality using the grading of recommendations assessment, development and evaluation (GRADE) system, and disagreements were resolved by consensus.Results We identified 11 articles meeting our inclusion criteria. Only the randomized controlled trial (RCT) showed no significant difference in late axial pain (at 12 months) when C7 spinous muscle preservation was compared with no preservation. However, seven other retrospective cohort studies showed significant pain relief in the preserved group compared with the nonpreserved group. The preservation group included those with preservation of the C7 spinous process and/or attached muscles, the deep extensor muscles, or C2 muscle attachment and/or C3 laminectomy (as opposed to laminoplasty). One study that included preservation of either the C2 or C7 posterior paraspinal muscles found that only preservation of the muscles attached to C2 resulted in reduced postoperative pain. Another study that included preservation of either the C7 spinous process or the deep extensor muscles found that only preservation of C7 resulted in reduced postoperative pain.Conclusion Although there is conflicting data regarding the importance of preserving C7 and/or the semispinalis cervicis muscle attachments to C2, there is enough evidence to suggest that surgeons should make every attempt to preserve these structures whenever possible since there appears to be little downside to doing so, unless it compromises the neurologic decompression.
Keywords: laminoplasty; axial neck pain; C7 preservation; semispinalis cervicis; C3 laminectomy